Analysis of Sand Volleyball Coaching Management - Ramadhan, Trias; Rustandi, Endi; Priyono, Ali (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
Leadership is one of the factors that can affect sports achievement. The purpose of this study is to find out what achievement development management is like in sandball sports. The purpose of this study was to determine the management analysis of beach volleyball training in Indramayu Regency. The research method used is descriptive and based on a sample of 25 people. In collecting data, researchers used a questionnaire that had previously been tested for validity and reliability. By using descriptive statistical data analysis techniques, the results obtained from the analysis of the management study of sand volleyball development in Kab. Indramayu is included in the good category